2013
DOI: 10.7202/1014951ar
|View full text |Cite
|
Sign up to set email alerts
|

Les interventions infirmières estimées bénéfiques par les adolescents à risque de suicide

Abstract: Cette recherche identifie les interventions infirmières bénéfiques selon la perspective des adolescents à risque pour suicide. Quoique les infirmières du milieu hospitalier aient un niveau de contact direct, élevé et continu auprès du patient, il n’existe aucune recherche sur les interventions thérapeutiques offertes par ces dernières. Cette étude qualitative a pour but d’avancer nos connaissances quant au rôle de l’infirmière dans le rétablissement des adolescents suicidaires lors une hospitalisation psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Mental health nurses work to empower clients and families using a broad range of biophysical, interpersonal, and environmental interventions (Pugnaire Gros et al . ). These are applied in the context of everyday interactions and daily care, and are offered in response to the presenting life challenges and health concerns of clients and families.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mental health nurses work to empower clients and families using a broad range of biophysical, interpersonal, and environmental interventions (Pugnaire Gros et al . ). These are applied in the context of everyday interactions and daily care, and are offered in response to the presenting life challenges and health concerns of clients and families.…”
Section: Discussionmentioning
confidence: 97%
“…; Pugnaire Gros et al . ). Specific clinical skills, such as observing, active listening, mindful presence, and accompaniment, are required in order for the nurse to develop a deep understanding of the client and family's experiences and perspectives.…”
Section: Relevance For Clinical Practicementioning
confidence: 97%
See 1 more Smart Citation
“…The study by Klausner et al (2000) showed a decrease in depression and anxiety in elderly people with depression through hope-based group intervention. Other studies have highlighted a concomitant impact on both family and patient of interventions based on strengths and collaborative partnerships (Ezer et al, 1997;Gottlieb & Rowat, 1987;Gros et al, 2012).…”
Section: Response To Family Expectations Through Gottlieb's Theory Of Forcementioning
confidence: 99%